حل جديد لمشكلة المنتجات غير المرمزة باستخدام تقنيات قواعد المعطيات والبرمجة (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
The problem has been addressed in this article is general and common problem in the area of the wholesale trade and retail trade in particular. This problem comes through non-barcoded products or products that cannot be coded before they are sold, such as milk, rice, ...etc. Many studies have been found to solve this problem by using one of two principles. The first principle depends on the abstract technical method using devices to generate the barcode (or special programs to perform a task to generate the barcode), and then re-entered the new data from generated barcode into the using accounting system. The second principle depends on a dynamic way to create a list of non-barcoded products with these barcodes, which are previously stored in the using program. Then the user must enter this information manually to the user interface program. Both principles possess disadvantages; have been processed in our own way put forward in this article. Nowadays, no one can make wonderful works for the practice without database technologies. We use in this article some database techniques to build database system with its necessary relationships. Then we have supported this system with views (interfaces) to avoid the disadvantages of both mentioned principles and use these positive points. Through these interfaces we can determine the non-barcoded product, and to enter the quantities with prices showing a view where we can enter the quantity, price or force it to take together. We can understand by the application of these interfaces to address the problem of lost or quantities of products dedicated to the customer. We addressed and processed all these points through the algorithm XOMA, defined by us and is not supported by any use of accounting system. إن المشكلة التي تمّ تناولها في هذا المقال هي مشكلة عامة وشائعة في مجال تجارة التجزئة بشكل خاص وتجارة الجملة بشكل عام. وتنشأ هذه المشكلة من خلال المنتجات الغير مرمزة أو التي لا يمكن ترميزها قبل بيعها مثل الحليب، الرز، ... الخ. وُجدت دراسات كثيرة لحل هذه المشكلة باستخدام احد مبدأين. يعتمد المبدأ الأول على طريقة تقنية مجردة باستخدام أجهزة لتوليد الباركود (أو برامج خاصة لتنفيذ مهمة توليد الباركود)، ويتم إعادة قراءته من جديد ليتم إدخال بياناته لنظام المحاسبة المُستخدم. أما المبدأ الثاني فيعتمد على طريقة ديناميكية بإنشاء قائمة تحوي على المواد غير المرمزة لدى التاجر مع ترميزاتها المخزنة مسبقاً في البرنامج المستخدم للمحاسبة، وعلى المستخدم إدخال هذه المعلومات بشكل يدوي إلى واجهة البرنامج المستخدم. كلا المبدأين يملكان سلبيات تمت معالجتها بطريقتنا المطروحة في هذا المقال. في هذه الأيام لا يمكن لأحد أن ينجز أعمالاً رائعة في الجانب التطبيقي العملي بدون تقنيات قواعد المعطيات. تمّ في هذا العمل استخدام بعض تقنيات قواعد المعطيات لبناء نظام قواعد معطيات وعلاقاته اللازمة. ومن ثمَّ تمّ دعم هذا النظام بعدة واجهات لتجاوز السلبيات في المبدأين السابقين الذكر والاستفادة من النقاط الإيجابية فيهما. من خلال هذه الواجهات يمكننا أن نحدد المنتج غير المرمز، ولتحديد الكميات مع أسعارها تظهر نافذة نستطيع فيها إدخال الكمية أو السعر أو إجباره على المدخلتين معاً. مما يمكن فهمه من تطبيق هذه الواجهات أننا نستطيع معالجة مشكلة كميات المنتجات المفقودة أو المهداة للمستهلك. تمت معالجة جميع هذه النقاط من خلال خوارزمية XOMA المعرفة من قبلنا و الغير مدعومة من قبل أي نظام محاسبة مستخدم.